MULTIPLE STRATEGIES AS OPTIMAL CONTROL OF A COVID-19 DISEASE WITH QUARANTINE AND USING HEALTH MASKS - Hakim, Lukman (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
This research develops an optimal control as an effort to push down the widely of Covid-19 with a mathematical model. Where, the problem of optimal control is conducted by adding three control variables, i.e an effort to avoid direct contact between the susceptible populations without masks and the infected populations without masks, and the thoughtfulness of a mask-wearing policy. The primary goal of optimal control is to minimize the infected populations without and with masks, and minimize the cost of weight control. Furthermore, if it applies Pontryagin's principle and discovers the Hamiltonian function, then optimal control conditions for the COVID-19 approximation are determined. Finally, as an addition to the model analysis results, numerical simulations are conducted to represent the solutions behavior of each subpopulation before and after the control was designed.